Spatial and seasonal variation of pollution sources in proximity of the Jaranman-Saryangdo area in Korea. (15th February 2017) - Jung, Yeoun Joong; Park, Young Cheol; Lee, Ka Jeong; Kim, Min Seon; Go, Kyeong Ri; Park, Sang Gi; Kwon, Soon Jae; Yang, Ji Hye; Mok, Jong Soo
Abstract: We aimed to compare the spatial and seasonal distributions of fecal coliforms (FCs) and other physiochemical factors in the drainage basin of the Jaranman-Saryangdo area. Among the pollution sources, the mean daily loads and half-circle radii of FCs were the highest in June. However, the pollutants did not reach the boundary line of the designated area due to an existing buffer zone. The value of the FC geometric mean at station 1 was highest in August during periods of heavy rainfall; however, this value was lower than the regulation limit. The highest daily loads of chemical oxygen demand (COD) and chlorophyll- a (Chl- a ) in seawater were in the surface layer in August; however, dissolved oxygen (DO) in the bottom water layer was at its lowest in August. This study demonstrated that season and rainfall have significant effects on the FC, COD, DO, and Chl- a concentrations in seawater. Highlights: The Jaranman-Saryangdo area can be easily contaminated by various drainage sources. The geometric mean for FCs was at its maximum in August periods of heavy rainfall in Korea. Season and rainfall have significant effects on the FC and physiochemical factors.